Development Of Scoring Rubric To Assess Students’ Creativity In Engineering Technology - Maimunah , Husien (2014)
Creativity has become very important to the Malaysian Education System. The inclusion of creativity construct into the Standard Curriculum for Primary School (KSSR) gives the indication that the government is committed toward the inculcation of creativity among student. To achieve such target, pedagogy and assessment must be upgraded. Kreativiti telah menjadi sangat penting kepada Sistem Pendidikan Malaysia. Kemasukan konstruk kreativiti ke dalam Kurikulum Standard Sekolah Rendah (KSSR) menunjukkan bahawa kerajaan komited ke arah memupuk kreativiti dalam kalangan pelajar. Bagi mencapai sasaran tersebut, kedua-dua pedagogi dan penilaian perlu dipertingkatkan.